2022
DOI: 10.3390/cancers14174323
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients Treated with Pembrolizumab as a Second-Line Treatment for Advanced Biliary Tract Cancer

Abstract: Some BTC types respond to pembrolizumab, but there are no known prognostic factors to predict its treatment benefits. In this study, we attempted to identify the prognostic factors associated with pembrolizumab as a second-line treatment for gemcitabine-refractory BTC. This retrospective and single tertiary-center study involved all the consecutive patients (n = 80) with refractory advanced BTC, who were diagnosed as programmed cell death ligand 1-positive and treated with pembrolizumab between August 2017 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In our study, MSI-H status was a protective factor for both OS and PFS of immunotherapy in multivariate analysis. However, another study found that MSI-H ( N = 15) was not an independent protective factor ( P = 0.162) in refractory CCA with PD-L1 positivity (CPS≥ 1 or tumor proportion score (TPS) ≥ 1%) and treated with pembrolizumab, indicating that PD-L1 expression is also another important confounding factor [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, MSI-H status was a protective factor for both OS and PFS of immunotherapy in multivariate analysis. However, another study found that MSI-H ( N = 15) was not an independent protective factor ( P = 0.162) in refractory CCA with PD-L1 positivity (CPS≥ 1 or tumor proportion score (TPS) ≥ 1%) and treated with pembrolizumab, indicating that PD-L1 expression is also another important confounding factor [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyerim Ha1 et al [ 26 ] found that patients with high levels of NLR, PLR, and SII had poorer OS by analyzing the hematological indicators of 158 patients with advanced BTC. Chan Su Park et al [ 27 ] also found in a retrospective study that lower MLR was significantly associated with better OS in patients with advanced BTC treated with pembrolizumab in the second line. This result is consistent with the results in the retrospective study we conducted, in which we also found a significant correlation between lower NLR ( p = 0.0083), PLR ( p = 0.020), SII ( p = 0.0161), and MLR ( p < 0.001) and better OS of patients.…”
Section: Discussionmentioning
confidence: 99%